2000
DOI: 10.1002/1529-0131(200001)43:1<22::aid-anr4>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting response to treatment in rheumatoid arthritis: The importance of disease duration

Abstract: RA patients with longer disease duration do not respond as well to treatment compared with patients with early disease, and female sex, prior DMARD use, disease functional class, and disease activity also have effects on the likelihood of patient response to treatment. This has implications for trial interpretation and for the clinical expectations of RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
209
4
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(246 citation statements)
references
References 17 publications
15
209
4
13
Order By: Relevance
“…Baseline variables possibly influencing the patient's disease state and MTX response were selected based on the literature (10)(11)(12)(13)(14)(15)(16)(17)(18)20,23,27,28). The following factors were iden-tified: sex; rheumatoid factor (RF) status; age; duration of joint symptoms; alcohol consumption; smoking; body mass index; menopausal status; hormone supplementation; scores for physician's assessment of disease activity, pain, patient's assessment of disease activity, patient's assessment of global health, and morning stiffness on a 0-100-point VAS; Health Assessment Questionnaire (HAQ) score (29); ESR; C-reactive protein level; DAS; SJC; RAI; kidney function (defined as creatinine clearance); anti-cyclic citrullinated peptide (anti-CCP) status; NSAID use; and the existence of comorbidity based on drug use (other than RA disease-related drugs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline variables possibly influencing the patient's disease state and MTX response were selected based on the literature (10)(11)(12)(13)(14)(15)(16)(17)(18)20,23,27,28). The following factors were iden-tified: sex; rheumatoid factor (RF) status; age; duration of joint symptoms; alcohol consumption; smoking; body mass index; menopausal status; hormone supplementation; scores for physician's assessment of disease activity, pain, patient's assessment of disease activity, patient's assessment of global health, and morning stiffness on a 0-100-point VAS; Health Assessment Questionnaire (HAQ) score (29); ESR; C-reactive protein level; DAS; SJC; RAI; kidney function (defined as creatinine clearance); anti-cyclic citrullinated peptide (anti-CCP) status; NSAID use; and the existence of comorbidity based on drug use (other than RA disease-related drugs).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the influences of demographic, clinical, immunologic, and genetic factors on the state of disease in patients with RA have been studied (10)(11)(12)(13)(14)(15)(16)(17)(18). Specifically, polymorphisms in genes coding for methylenetetrahydrofolate reductase (MTHFR), adenosine monophosphate deaminase (AMPD1), aminoimidazole carboxamide ribonucleotide transformylase (ATIC), serine hydroxymethyltransferase 1 (SHMT1), and inosine triphosphate pyrophosphatase (ITPA) demonstrate association with the MTX response (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…There is growing evidence that therapeutic intervention early in the disease course of rheumatoid arthritis (RA) leads to earlier disease control and less joint damage (1)(2)(3)(4)(5)(6). Since treatment with disease-modifying antirheumatic drugs (DMARDs) is only justified when the risk:benefit or cost-effectiveness ratios are favorable, it is mandatory to be able to differentiate between RA and other forms of arthritis early after symptom development (7).…”
mentioning
confidence: 99%
“…9 Studies have clearly demonstrated that response to DMARD therapy is related to duration of symptoms prior to diagnosis. 10 The diagnosis of rheumatoid arthritis can be made with normal autoantibodies/inflammatory markers. Primary care physicians should not wait for investigation results prior to referral if rheumatoid arthritis is suspected.…”
Section: Managementmentioning
confidence: 99%
“…Where combination DMARDs are not suitable, rapid uptitration of monotherapy should be considered. 10 Disease control is generally assessed using the Disease Activity Score (DAS28; see Table 2), which is a composite score that includes clinician assessed tender and swollen joints, a visual analogue scale (VAS) and measurement of either erythro cyte sedimentation rate (ESR) or C reactive protein (CRP) (both blood markers of inflammation). Treatment is titrated as per the DAS28 score.…”
Section: Azathioprinementioning
confidence: 99%